Transient characteristics of mobile transformer vehicle bypass operation - Zhou, Lei; Feng, Xiao; Chen, Xi; Fu, Hongquan; Bian, Changhao; Jing, Yang; Wu, Shaocheng (Frontiers in Energy Research, 2023)
The bypass operation method of mobile transformer vehicles is a common method for maintenance or replacing transformers in distribution lines, which could avoid power outages and ensure the reliability of electricity consumption. However, the transient characteristics of mobile transformer vehicles connected to the grid can have an impact on the power quality of the grid. In response to this problem, a model is built based on the MATLAB/Simulink to model the process of grid-connection. The simulation analyzed the current and voltage waveforms of the transient process of grid connection. Moreover, a combination of time domain and frequency domain analysis was used to analyze the transient overvoltage and overcurrent conditions of the grid connection. Finally, the effects of two overcurrent suppression methods, adjustment of closing angle method and series closing resistance method, were analyzed. These studies can provide theoretical guidance for engineering applications.